2009
DOI: 10.1095/biolreprod.108.069203
|View full text |Cite
|
Sign up to set email alerts
|

Survival Role of Locally Produced Acetylcholine in the Bovine Corpus Luteum1

Abstract: The present study was conducted to explore the source of acetylcholine (ACH) in the corpus luteum (CL) and to test our hypothesis of an antiapoptotic role of ACH in the bovine CL and, further, to investigate whether nerve growth factor (NGF), insulin-like growth factor 1 (IGF1), and transforming growth factor beta1 (TGFB1) influence the expression of choline acetyltransferase (CHAT), the biosynthetic enzyme of ACH, in cultured bovine luteal cells. Protein expression and immunolocalization of CHAT were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
3
13
0
Order By: Relevance
“…In pig, the increased NGF and TrkA protein levels in luteal cells were found during the estrous cycle [35]. These results shed light to the critical role of NGF in development and/or maintenance of luteal function, which is further supported by the findings that NGF can stimulate of progesterone and oxytocin release [40] and acetylcholine production [41] in bovine luteal cells as well as maintenance of luteal vasculature in rats [37]. In line with these aforementioned data, our present results indicated that NGF ligand and receptors might play a similar role in the development of corpora lutea in the wild seasonally-breeding rodent.…”
Section: Discussionmentioning
confidence: 85%
“…In pig, the increased NGF and TrkA protein levels in luteal cells were found during the estrous cycle [35]. These results shed light to the critical role of NGF in development and/or maintenance of luteal function, which is further supported by the findings that NGF can stimulate of progesterone and oxytocin release [40] and acetylcholine production [41] in bovine luteal cells as well as maintenance of luteal vasculature in rats [37]. In line with these aforementioned data, our present results indicated that NGF ligand and receptors might play a similar role in the development of corpora lutea in the wild seasonally-breeding rodent.…”
Section: Discussionmentioning
confidence: 85%
“…EGR1 is regarded as a master transcription factor and is linked to differentiation and mitosis. Furthermore, a previous study showed that NGF increased levels of CHAT in bovine luteal cells [37]. This enzyme is important for the production of ACh from GCs and was also described in the human ovary and GCs [29, 38-40].…”
Section: Discussionmentioning
confidence: 98%
“…ACh in the ovary acts as a trophic molecule and regulates ion channel activity in human GCs [40]. In the bovine corpus luteum (CL) [37] it was also reported to exert anti-apoptotic actions. Thus NGF appears to be a trophic factor for human GCs.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of IFNG on luteal cells are potentiated in the presence of TNF, 66,72 probably because of TNF‐induced upregulation of IFNG receptors 74 . Induction of apoptosis by IFNG + TNF can be suppressed by IFNA or acetylcholine, 75,76 and progesterone may confer some protective effect against apoptosis in the CL 77 …”
Section: Cytokine Expression and Actions In The CLmentioning
confidence: 99%